قياس اتجاهات الرأي لدى طلاب الصف الثالث الثانوي نحو التعليم الخاص وتكلفته المادية - شملص, عفيفة (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The study of measuring the student s opinion about the private education in special centers has taken an urgent need because of its great effect on the development of the human resources being considered an attrition factor for the family income in Lattakia and in order to know the students trends, we token sample about 300 students of both the literary and scientific section .This sample used as a tool to measure the students trends . This study has concluded to prove most of the search hypothses and also show the most important factories which attract the students to the private education. After measuring there trends the scientific teacher experience where the relative importance of the students answers has reached 84.6%, as well as the high confession in the university every year has taken the relative importance of this point 89.2% .The students desire of achieving his dream to enter the university had reached 81.4% .The study also has found statistically significant differences between the cost of the student in scientific part and literary one. تعد دراسة قياس اتجاهات رأي طلاب الصف الثالث الثانوي نحو التعليم الخصوصي في المراكز الخاصة، ضرورة ملحة لأثرها البالغ الأهمية على تنمية الموارد البشرية المستقبلية ، وكونها تعتبر عامل استنزاف لدخل الأسر في مدينة اللاذقية ، ولمعرفة اتجاهات الطلبة نحو التعليم الخاص سحبت عينة قصدية بلغ حجمها 300 طالبا من الصف الثالث الثانوي بفرعيه، واستخدمت الاستبانة كأداة لقياس اتجاهات الطلبة ، وقد توصلت الدراسة إلى إثبات معظم فرضيات البحث ، كما أظهرت الدراسة أن من أهم العوامل التي تجذب الطلبة إلى التعليم الخاص وفق قياس اتجاهاتهم خبرة المدرس العلمية والتدريسية، حيث وصلت الأهمية النسبية لإجابات الطلبة إلى 84.6 % ، وكذلك ارتفاع المعدل الجامعي في كل عام وبلغت الأهمية النسبية 89.2 %، و رغبة الطالب في تحقيق حلمه في تسجيل فرعه في المرحلة الجامعية فبلغت 82.4 % ، كما توصلت الدراسة إلى وجود فروق دالة احصائيا بين تكلفة الطالب في الفرع العلمي، وتكلفته في الفرع الأدبي.